Analisis ergonomi lingkungan kerja fisik pada karyawan bagian laboratorium produksi - Mukhtar, M Nushron Ali; Yafi, M Ali; Abdurrasyid, Hakeem; Ramadhan, Adhitya Firmansyah (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
This research aims to analyze the impact of the physical work environment on employee performance at company X. An optimal physical work environment is identified as a key factor in increasing employee productivity and satisfaction. Through a quantitative approach, data is collected through employee surveys and physical work environment observations. An in-depth discussion of the implications of the findings for improving the physical work environment and company policies will be presented. This research is expected to make an important contribution to understanding the role of the physical work environment in improving employee performance, as well as providing a basis for companies to develop appropriate improvement strategies. The conclusion highlights the urgency of paying attention to the physical work environment as an investment to achieve optimal performance and employee satisfaction at company . These results show a figure of 71.2 dBA in noise calculations and 13.84 or 14 light points in lighting calculations, all of which indicate that the room is ergonomic enough for employees.